DEFAULT/BREACH OF CONTRACT CHARACTERISTICS OF MUDHARABAH FINANCING IN SHARIA BANKING - Usanti, Trisadini Prasastinah; Raden Roro, Fiska Silvia (Journal of Islamic Law Studies, 2021)
One of financings channeled by Sharia Bank is mudharabah. The contract of mudharabah is a mutual agreement between the first party (malik, shahibul maal, or Sharia Bank) which supports the whole capitals and the second party (‘amil, mudharib, or Customer) which acts upon fund endowment by sharing the profit in accordance with the agreement stated in the contract, while the loss is fully covered by Sharia Bank unless the customer (mudharib) makes an intentional mistake, in negligence or violates the agreement. Mudharib in the contract of mudharabah acts upon amin (the trusted one). The capital given is a mandate being held by mudharib. Mudharib is as the representative. The position of mudharib as the representative is trusted by shahibul maal in running the business and Mudharib as a partner in earning the profit. Mudharib will get the share of the profit from the business run. Mudharabah financing is a financing that shares the profit and loss, therefore if mudharib in fund endowment finds failure not under his intention and his failure does not cause profit share in accordance with the profit share ascribed, thus mudharib cannot be sentenced as being default/breach of contract of mudharabah as it is characterized in default/breach of contract. The criteria of default/breach of contract is when the customer does not follow the agreement or he does based on the agreement yet not as well as it is agreed or he follows what is agreed yet overdue or does something prohibited in the agreement